Letter from Carl D. Duncan to Patricia Whiting, August 23, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan expresses his love and admiration for Patricia Whiting and shares his experiences while traveling to Chicago.